Factors influence product preference among Middle East consumer / Nadzrin Azri Nor Azmi - Nor Azmi, Nadzrin Azri (Faculty of Business and Management, 2014)
The purpose of this study is to identify the factor influence product preference among Middle East consumer. The research is based on a sample of 40 respondents who bought Malaysia product at least for the last 6 months, Jun 2013 until November 2013.The results show that product attributes, branding, packaging and labeling have significant relationship with product preference. However, only product attributes have significant influence towards product preference among Middle East consumer. While branding, packaging and labeling did not have significant influence towards product preference.